Efektivitas media zep quiz dengan model pembelajaran teams games tournament terhadap motivasi dan hasil belajar matematika di PKBM putra bangsa Demak - Amajida, Aufar; Khoiri, Nur; Rozzaqi, Ade Ricky (Papanda Journal of Mathematics and Science Research, 2025)
This study aims to determine the effectiveness of applying Zep Quiz media with the Team Games Tournament (TGT) cooperative learning model on students' motivation and cognitive learning outcomes, particularly on the topic of ratios at PKBM Putra Bangsa Demak. The background of this study is rooted in the observation that students demonstrated a lack of learning motivation and low learning outcomes. This study employed a quantitative descriptive approach. The research utilized a pre-experimental method with a One Group Pretest-Posttest design. Data collection techniques included pretests-posttests, questionnaires, and interviews. The results showed an N-Gain score (0.59) higher than the established indicator (0.3), signifying that mathematics learning on the topic of ratios using Zep Quiz media with the TGT model was effectively implemented, achieving a moderate N-Gain score. The use of Zep Quiz media also influenced students' learning motivation. The average student learning motivation before implementing Zep Quiz with the TGT model was 63% (sufficient category), whereas after the implementation, it increased to 93% (very good category). This indicates that learning with Zep Quiz media and the TGT model impacts students' motivation and cognitive learning outcomes, and is classified as effective with a moderate level of improvement. Therefore, quiz-based digital media has been proven to be an innovative solution for the mathematics learning process in the digital era.